Pemodelan Homologi Komparatif Struktur 3d Protein dalam Desain dan Pengembangan Obat - Saudale, Fredy Z (Al-Kimia, 2020)
One of the strategies applied in the initial steps of drug design and discovery is by utilizing the availability of 3D protein structures. However, most of functional protein structures have not been fully obtained experimentally to date. This is due to the difficulty of procedures, the high cost and the length of time required from structural biology experiments such as X-ray crystallography. Comparative homology modeling is a computational method that is proven to be accurate in predicting the structure of 3D target proteins with a ratio of 30% similarity to the arrangement of amino acids in the structure of the template proteins. This review attempts to explain comparative homology modeling methods such as MODELLER, PHYRE2, SWISS-MODEL, its iterative steps in predicting and building 3D protein target models, its evaluation and validation of protein models as well as the examples of their application in drug design and development targeting GPCR proteins, Zika virus RNA polymerase and HIV protease. With this, comparative homology modeling can be very useful to accelerate research on drug design and development in dealing with diseases and health problems that still exist in the society.